2019
DOI: 10.1029/2019gl084792
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Exsolution and Bubble Formation in Titan's Lakes

Abstract: Titan's surface liquids are composed primarily of methane, ethane, and dissolved atmospheric nitrogen. The nitrogen content depends on the alkane composition and temperature, and exsolves as bubbles when these parameters are sufficiently perturbed. Herein, we present an experimental study of nitrogen bubbles in methane-ethane liquids, and propose that both methane and ethane are required for bubbles to form under Titan conditions. Bubbles occur when methane composes 40-95 mol% of the alkanes within the liquid.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…If instead we ascribe the low values of sea surface backscatter recorded on Moray Sinus to an effect of sea surface roughening (the second scenario), and consider a sea surface permittivity of ε s = 1.7, we would require an increase of effective sea surface RMS roughness σ h from the 0.9 ± 0.3 mm of northern Ligeia Mare (see also [Zebker et al, 2014]) to 2.4 ± 0.1 mm in Moray Sinus. Note that nitrogen exsolution in the form of bubbles at the surface of the sea, caused by outflow from methane-nitrogen rivers mixing with more ethanerich lakes or seas as proposed by Malaska et al (2017) and Farnsworth et al (2019), would potentially have two effects: a decrease in the effective permittivity (because of the presence of the empty space within the bubbles themselves), and an increase the effective roughness of the sea surface. Moray Sinus could be such an area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If instead we ascribe the low values of sea surface backscatter recorded on Moray Sinus to an effect of sea surface roughening (the second scenario), and consider a sea surface permittivity of ε s = 1.7, we would require an increase of effective sea surface RMS roughness σ h from the 0.9 ± 0.3 mm of northern Ligeia Mare (see also [Zebker et al, 2014]) to 2.4 ± 0.1 mm in Moray Sinus. Note that nitrogen exsolution in the form of bubbles at the surface of the sea, caused by outflow from methane-nitrogen rivers mixing with more ethanerich lakes or seas as proposed by Malaska et al (2017) and Farnsworth et al (2019), would potentially have two effects: a decrease in the effective permittivity (because of the presence of the empty space within the bubbles themselves), and an increase the effective roughness of the sea surface. Moray Sinus could be such an area.…”
Section: Discussionmentioning
confidence: 99%
“…(2017) and Farnsworth et al. (2019), would potentially have two effects: a decrease in the effective permittivity (because of the presence of the empty space within the bubbles themselves), and an increase the effective roughness of the sea surface. Moray Sinus could be such an area.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experiments, thermodynamics models, and molecular simulations suggest that the liquid hydrocar-bon bodies on the surface are major sinks of nitrogen [8][9][10][11]. Most of these experiments were motivated by the detection of transient bright features by Cassini RADAR system, also known as "Magic Islands" [12,13].…”
mentioning
confidence: 99%
“…Various scenarios for the exsolution of nitrogen in the form of bubbles were hypothesized, including superheating, supersaturation, titration of ethane into methane rich regions [8,15]. Explicit experiments on the bubble formation in Titan-like conditions were recently performed and authors found several criteria for the formation of bubbles on Titan [9]. The focus of many of these experiments have solely been the solubility of nitrogen and exsolution of nitrogen from the lakes and seas of Titan [8,9].…”
mentioning
confidence: 99%
See 1 more Smart Citation